The Effectiveness of the Android-Assisted Information Service Model to Enhance Students' Understanding of Academic Resilience - Gumelar, Fikri Arif; Wibowo, Mungin Eddy; Awalya, Awalya (Jurnal Bimbingan Konseling, 2023)
Academic resilience is an individual’s ability to survive and recover in difficult conditions. Many studies conclude that academic resilience assists students in dealing with learning difficulties, improving achievement, reducing anxiety at school, school fatigue and the habit of skipping school. Regarding these issues, the present study aimed at testing the effectiveness of the Android-assisted information service model to enhance students’ understanding of academic resilience. It was a quasi-experimental study which used a non-equivalent control group design to determine the level of effectiveness of treatment in the control and experimental groups. The treatment was in the form of media and guides have been validated by experts with excellent and feasible results. Following the data collection, the analysis was carried out using a paired sample t-test. Subjects in the experimental group (59 students) and the control group (51 students) had relatively similar initial academic resilience scores. Based on the findings, the Android-assisted information service model has been effective in enhancing the understanding of academic resilience in students at SMP Negeri 19 Semarang. Further researchers are recommended to add game and data management features to the Android products being developed.